In silico Single-Cell Analysis of Steroid-Responsive Gene Targets in the Mammalian Cochlea - Nelson, Lacey; Lovett, Braeden; Johns, J. Dixon; Gu, Shoujun; Choi, Dongseok; Trune, Dennis; Hoa, Michael (Frontiers in Neurology, 2022)
BACKGROUND: Treatment of many types of hearing instability in humans, including sudden sensorineural hearing loss, Meniere’s disease, and autoimmune inner ear disease, rely heavily on the utilization of corticosteroids delivered both by systemic and transtympanic routes. Despite this use, there is heterogeneity in the response to corticosteroid treatment in humans with these diseases. The mechanisms by which corticosteroids exert their effect and the cell types in which they exert their effects in the inner ear remain poorly characterized. In this study, we localize steroid-responsive genes to cochlear cell types using previously published transcriptome datasets from the mammalian cochlea. METHODS: Steroid-responsive genes were localized to specific cochlear cell types using existing transcriptome datasets from wild-type mammalian cochlea exposed to systemic and transtympanic steroids, as well as previously published single-cell and single-nucleus RNA-sequencing datasets from the mammalian cochlea. Gene ontology (GO) analysis of differentially expressed genes (DEGs) was performed using PANTHER to investigate cellular processes implicated in TT versus systemic steroid action in the cochlea. RESULTS: Steroid-responsive genes were localized to specific cell types and regions in the cochlea including the stria vascularis, organ of Corti, and spiral ganglion neurons. GO analysis demonstrated steroid-responsive DEGs in the spiral ganglion neurons to be associated with angiogenesis, apoptosis, and cytokine-mediated anti-inflammatory pathways. CONCLUSIONS: Single-cell and single-nucleus transcriptome datasets localize steroid-responsive genes to specific regions in the cochlea. Further study of these regionally-specific steroid-responsive genes may provide insight into the mechanisms of and clinical response to corticosteroids in diseases of hearing instability.